Multi-Objective Optimization of a Direct-Drive Dual-Structure Permanent Magnet Machine - Ma, Yue; Ching, T. W.; Fu, W. N.; Niu, Shuangxia (IEEE transactions on magnetics, 2019)
The purpose of this paper is to optimize the design of a dual-structure permanent magnet (PM) machine for the low-speed application. Multi-objective optimization using nondominated sorting genetic algorithm II (NSGA-II) is used to maximize the torque and efficiency while reducing the torque ripple of the machine. The torque, torque ripple, and efficiency of the optimized machine have significant improvement by optimizing the machine parameters within a fixed outer axial and radial length. This optimization process can be used to select the best machine design in different aspects' requirement.